Nurse provision of support to help inpatients quit smoking. (19th December 2016) - Malone, V.; Ezard, N.; Hodge, S.; Ferguson, L.; Schembri, A.; Bonevski, B.
Abstract : Issue addressed: Identification of the factors that facilitate nurses to provide smoking cessation advice to hospitalised patients. Method: Six semistructured focus groups with 26 nurses were conducted in June 2015. Participants completed a structured survey to collect patient demographic data and assess attitudes towards their role in addressing smoking cessation among inpatients. Results: Important themes that emerged from the qualitative data were: nurses' negative perceptions of smokers, nurses' confidence in their knowledge of smoking cessation care and nurses' uncertainty around whose role it is to provide smoking cessation care. Conclusion: Nurses require training in order to confidently and competently address smoking among inpatients as part of routine care. Formal ways to document the smoking status of inpatients and the offer of smoking cessation support from a nurse to an inpatient would enhance the communication between nurses around which inpatients had been asked about their smoking status and which had not. For patients who are resistant to conventional cessation strategies, innovative ways are needed to reduce the harm caused to them by tobacco use. So what?: Nurses need to be provided with education and training around smoking cessation to increase their confidence and skills to provide smoking cessation care to inpatients. Abstract : Smoking has been linked to an increased risk for cancers and cardiovascular disease. This study engaged hospital nurses to find out why routine smoking cessation care was not provided. Nurses did not have confidence in their knowledge and skills in smoking cessation to support patients to quit smoking. Education and training in smoking cessation best practice should be available to all nursing staff.